BANGUNAN FILSAFAT POLITIK TENTANG CIVIL SOCIETY DALAM PEMIKIRAN THOMAS HOBBES - Tajuddin, Muhammad Saleh (Jurnal Diskursus Islam, 2013)
Hobbes shows human as negative aspect, where human instinc tend to conflict, and war. So, sovereignty has to give state leader absolutely in order the state become strong and every state has to coperate with other in commonwealt paradigm. Hobbes discusses the concept of civil society starting with the concept of human being as human nature, particularly the concept of self, individu, and society. Hobbes looks at that human nature is a creature that affected by irrational, anachy, jelious, and hate, so the human become rude, and bad. This situations are called as primitive civil society. Meanwhile, Hobbes depicts modern civil society as a contradiction with human nature and natural law. Hobbes explains that state is created by individu who want create a piece from human nature, so human being has to make a social contract among individu.